Effects of aerobic training and black carbon particles exposure on gene expression of NF-κB and TNF-α of hippocampus brain tissue of male rats - Batool Rezaee Seraji; Hamid Agha Alinejad; Reza Gharakhanloo; Masoomeh Ebtekar; Mohamad Fashi; Behzad Pakrad; Akram Karimi Asl (Shahid Beheshti University, 2018)
Purpose: The purpose of this study was to investigate the effect of aerobic exercise and black carbon particleson gene expression of NF-κB and TNF-α in rats.Methods: Twenty-four male Wistar rats with an average body mass 279.29±26.97 g were randomly dividedinto 4 groups A: without exposure PM10 and aerobic exercise, B: aerobic training, C: exposure to PM10carbon black (5 mg/m3; per rat), D: and aerobic exercise concomitantly with exposure to PM10 carbon black.Twenty-four hours after the last training session and exposure, the animals were sacrificed. Real timePcr technique was used. Two-way ANOVA and post hoc LSD was used to determine the significance ofdifferences between groups.Results: There was significant difference between groups A and B (P=0.001) and B and D (P=0.003) in theamount of TNF-α. Significant difference between A and B groups (P=0.008) in the amount of NF-κB wasobserved.Conclusions: four weeks of aerobic exercise and PM10 exposure lead to modify the inflammatory factors ofNF-κB and TNF-α. It seems that these changes lead to reducing the risk of neurodegenerative diseases.